2011
DOI: 10.1007/s00406-011-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

The psychosis continuum in the general population: findings from the São Paulo Epidemiologic Catchment Area Study

Abstract: The aim of the study was to examine the psychosis continuum in a Latin-American community setting. Data were from the Brazilian São Paulo Epidemiologic Catchment Area Study, a cross-sectional survey conducted in two boroughs of the city of São Paulo. The Composite International Diagnosis Interview (version 1.1) was applied to a probabilistic sample of 1,464 adults, who were interviewed in their household, in order to identify the presence of psychotic symptoms. A subsample was assessed with Schedules for Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 48 publications
2
26
0
13
Order By: Relevance
“…Depression sum scores correlated with the at-risk status for psychosis, which is in line with other reports (Loch et al, 2011;Yung et al, 2007), supporting the idea of a continuum between psychotic experiences and depression symptoms. However, an assessment of atrisk for psychosis is always categorical and is based on a cut-off point on risk assessment scales for some statistically predictive risk for psychosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Depression sum scores correlated with the at-risk status for psychosis, which is in line with other reports (Loch et al, 2011;Yung et al, 2007), supporting the idea of a continuum between psychotic experiences and depression symptoms. However, an assessment of atrisk for psychosis is always categorical and is based on a cut-off point on risk assessment scales for some statistically predictive risk for psychosis.…”
Section: Discussionsupporting
confidence: 87%
“…Yung et al (2007) reported with a clinical sample of adolescents that psychotic experiences decreased in a 6-month follow-up in conjunction with an improvement in depression level and with a remission of diagnosed mood disorder. A recent study by Loch et al (2011) suggests that depression is present on a continuum of different stages of psychotic experiences, as depression is present in a group of treatmentseeking subjects with clinically relevant hallucinations and delusions, and also in subjects who have no clinically relevant psychotic experiences. The idea of a continuum of psychotic experiences in general has been presented by other researchers (van Os et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…It is possible that the stress level of subjects has an infl uence on the level of psychosis risk symptoms. A study by Loch et al (2011) suggests that depression is present on a continuum of diff erent stages of psychotic experiences (in a study where depression was present in a group of treatment-seeking subjects with clinically relevant hallucinations and delusions, and also in subjects who had no clinically relevant psychotic experiences). In summary, help-seeking subjects in early intervention studies are not only symptomatic on a psychosis continuum, but also have diffi culties with functioning ability and QoL.…”
mentioning
confidence: 98%
“…They were measured by different rating scales and showed that greater symptom severity and worse insight were associated with worse functioning and stress further investigations on identifying treatment targets to improve social functioning in schizophrenia [7]. In a Brazilian catchment area, a psychosis continuum has been detected in a sample of 1,464 adults in order to identify psychotic symptoms [8]. Different risk factors have been identified influencing the manifestation of psychotic symptoms.…”
mentioning
confidence: 99%